Self-Efficacy in Patients With Hypertension and Their Perceived Usage of Patient Portals - Weai Ling Lim; Yi Ling Eileen Koh; Zhi En Tan; Yu Quan Tan; Ngiap Chuan Tan (SAGE Publishing, 2024)
Introduction: Self-efficacy in individuals optimizes their hypertension management. Electronic patient portals are being increasingly used to support chronic disease management, as they raise the health literacy of patients and enable them in self-management. However, the association between the use of patient portals and self-efficacy in hypertension management remains unclear. The study aimed to determine the association between self-efficacy among patients with hypertension who are managed in primary care and their demographic characteristics and usage patterns of patient portals. Method: A cross-sectional survey was conducted at a public primary care clinic in urban Singapore. Multi-ethnic adult patients with hypertension were invited to participate in a self-administered electronic questionnaire. Chi-square test was performed for bivariate analysis; adjusted logistic regression models were used for factors with P value <.1. Results: A total of 310 patients (66.8% Chinese, 55.5% males, mean age of 63.1 years) completed the survey. Patient portal users had higher self-efficacy scores than non-users (mean score=63 vs 60, maximum = 80, P  = .011). The factors associated with increased patient portal access included younger age <65 years (absolute odds ratio [AOR] = 2.634, 95%CI = 1.432-4.847; P  = .002), monthly income >$5000 (AOR = 2.324, 95%CI = 1.104-4.892; P  = .026), and post-secondary education level (AOR = 3.128, 95%CI = 1.675-5.839; P  < .001). Most patients (93.1%) used the portal to check medical appointments but only1.3% of them used it to record home blood pressure measurements (HBPM). Conclusions: Patient portal usage was associated with higher self-efficacy scores in patients with hypertension. These users were younger, more educated, and earned more than the non-users, but only 1.3% of them used it for HBPM documentation.